2006
DOI: 10.1111/j.1469-0691.2006.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in human immunodeficiency virus (HIV) RNA and CD4 cell counts among new entrants to HIV care

Abstract: Clinic database extraction identified 806 new entrants to human immunodeficiency virus (HIV) care in Cleveland, OH, USA. At entry, women had higher CD4 counts and lower HIV RNA levels than men (mean, 388 vs. 310 cells/microL, and 8.94 x 10(4) vs. 1.27 x 10(5) copies/mL, respectively), but the proportion of entrants with category C illnesses, category B conditions, sexually transmitted diseases and CD4 counts < 200 microL did not differ between genders. Hepatitis B seroprevalence was higher in men (8.7% vs. 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…Interestingly, sex differences in viral load are more pronounced in individuals with higher CD4 T cell counts, suggesting that differences in viral load might be lost at later disease stages(26). Furthermore, sex-specific differences in CD4+ T cell counts have been reported in several studies, with higher CD4+ T cell counts in HIV-1-infected women compared to men(2732). The precise mechanisms responsible for these reported sex differences in viral load and CD4+ T cell counts remain unknown.…”
Section: Sex Differences In Hiv-1-associated Immune Activation and Immentioning
confidence: 84%
“…Interestingly, sex differences in viral load are more pronounced in individuals with higher CD4 T cell counts, suggesting that differences in viral load might be lost at later disease stages(26). Furthermore, sex-specific differences in CD4+ T cell counts have been reported in several studies, with higher CD4+ T cell counts in HIV-1-infected women compared to men(2732). The precise mechanisms responsible for these reported sex differences in viral load and CD4+ T cell counts remain unknown.…”
Section: Sex Differences In Hiv-1-associated Immune Activation and Immentioning
confidence: 84%
“…As distinções de gênero observadas incluem características sócio-demográficas, fatores associados ao modo de exposição à infecção, o está-dio clínico em que se encontravam e os marcadores laboratoriais de importância prognóstica que exibiam ao iniciar o acompanhamento especializado. Analogamente ao descrito em outros países 10,11,12,13,14,15,16 , as mulheres avaliadas em São Paulo mostraram-se mais jovens que os homens ao diagnóstico de infecção por HIV. Sabe-se que a mucosa genital das meninas mais jovens é mais delgada e, portanto, mais vulnerável à aquisição do HIV 2 .…”
Section: Discussionunclassified
“…Apesar disso, na coorte estudada em São Paulo, não se observou diferença entre homens e mulheres no tempo decorrido entre o diagnós-tico de soropositividade e a admissão ao serviço especializado no cuidado a pessoas que vivem com HIV, à semelhança de relatos prévios relativos a pacientes austríacos 8 ou norte-americanos acompanhados nas regiões metropolitanas de Chicago e Cleveland 14,16 . Tal fato parece apontar em nossa série de casos para a inexistência de desigualdade de gênero no acesso ao cuidado especializado, talvez em função da universalidade do acesso ao cuidado e ao tratamento gratuito providos pelo sistema público de saúde em nosso país.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Some studies have found higher CD4 cell counts in women (36,37); other found higher CD4 cell counts in men (38), and still others found similar values in both sexes (39,40). It has also been reported that there are greater declines in CD4 cell counts in women (41) or no differences with men (42), as well as greater increases in CD4 cell counts following HAART in women (43) 3 ) in female which is in agreement with the higher CD4 cell counts observed in previous studies (36,37,45).…”
mentioning
confidence: 95%